(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In this globalized world, education has become an important means of expanding contacts between people. The Delores International Commission on Education in the Twenty-First Century report highlights the enormous potential of higher education to leverage globalization as a resource for bridging the knowledge gap and enriching intercultural dialogue. As a key factor in soft power and an important area of public diplomacy, international education can have numerous benefits, including the ability to create commercial value, advance a country’s foreign policy goals and interests, and facilitate economic growth and investment. The People’s Republic of China, known as the world’s most populous country and a global economic powerhouse, has prioritized the internationalization of its higher education system. This research paper analyzes China’s use of the education system as a soft power tool in foreign policy and its impact.